Do Weather-Induced Moods Affect the Processing of Earnings News? - DEHAAN, ED; MADSEN, JOSHUA; PIOTROSKI, JOSEPH D. (Journal of Accounting Research, 2017)
We investigate whether unpleasant environmental conditions affect stock market participants’ responses to information events. We draw from psychology research to develop a new prediction that weather-induced negative moods reduce market participants’ activity levels. Exploiting geographic variation in equity analysts’ locations, we find compelling evidence that analysts experiencing unpleasant weather are slower or less likely to respond to an earnings announcement relative to analysts responding to the same announcement but experiencing pleasant weather. Price association tests find evidence consistent with reduced activity due to weather-induced moods delaying equilibrium price adjustments following earnings announcements. We also use our analyst-based research design to re-examine an existing prediction that unpleasant weather induces investor pessimism, and find evidence of both analyst pessimism and reduced activity in the presence of unpleasant weather. Together, our study provides new evidence that both extends and reaffirms findings of a relation between unpleasant weather and market activities, and contributes to the broader psychology and economics literature on the impact of weather-induced mood on labor productivity.